2022
DOI: 10.3389/fonc.2022.987546
|View full text |Cite
|
Sign up to set email alerts
|

Early economic modeling of magnetic resonance image-guided high intensity focused ultrasound compared to radiotherapy for pain palliation of bone metastases

Abstract: IntroductionMagnetic Resonance Image-guided High Intensity Focused Ultrasound (MR-HIFU) is a non-invasive treatment option for palliative patients with painful bone metastases. Early evidence suggests that MR-HIFU is associated with similar overall treatment response, but more rapid pain palliation compared to external beam radiotherapy (EBRT). This modelling study aimed to assess the cost-effectiveness of MR-HIFU as an alternative treatment option for painful bone metastases from the perspective of the German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…An early economic modeling study demonstrated that adding MR-HIFU to RT regimes, independent of the sequence of treatment, resulted in better quality-adjusted life years (QALYs) and more durable pain response, compared with RT alone for pain palliation of bone metastasis. Furthermore, MR-HIFU has a 52% probability of being cost-effective compared with RT, according to probabilistic sensitivity analysis in the treatment of bone metastasis [53]. On the other hand, the shortcomings of HIFU include its long procedural time and the fact that it is limited to lesions that have unobstructed acoustic pathways, i.e., lesions that can be accessed and treated by HIFU and can be reached by a transducer.…”
Section: Discussionmentioning
confidence: 99%
“…An early economic modeling study demonstrated that adding MR-HIFU to RT regimes, independent of the sequence of treatment, resulted in better quality-adjusted life years (QALYs) and more durable pain response, compared with RT alone for pain palliation of bone metastasis. Furthermore, MR-HIFU has a 52% probability of being cost-effective compared with RT, according to probabilistic sensitivity analysis in the treatment of bone metastasis [53]. On the other hand, the shortcomings of HIFU include its long procedural time and the fact that it is limited to lesions that have unobstructed acoustic pathways, i.e., lesions that can be accessed and treated by HIFU and can be reached by a transducer.…”
Section: Discussionmentioning
confidence: 99%
“…For low-and intermediate-risk prostate cancer, active surveillance is more cost-effective than HIFU, but with high uncertainty [26]. In contrast, the use of HIFU as an alternative treatment for painful bone metastases might be cost-effective despite the considerable uncertainty [27]. Further exploration is needed regarding the cost-effectiveness of HIFU therapy for the treatment of breast cancer.…”
Section: Advantages and Disadvantages Of Hifu Therapy For Breast Cancermentioning
confidence: 99%
“…At the Central nervous system (CNS) level, clinical trials on HIFU-mediated medial or central lateral thalamotomies for neuropathic pain management were successfully conducted with long-term efficacies. Neuromodulation at the Peripheral nervous system (PNS) has given great success for the US-based management of cancer-induced pain [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%